Framing Jawi-Khat move: a comparative analysis of Chinese, English and Malay-language newspapers in Malaysia - Lee, Kenneth Tze Wui; Wong, Win Wei (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Malaysian government’s move to introduce Jawi-Khat in the Malay-language curriculum in Chinese and Tamil vernacular schools has been fraught with tension and opposition, especially among the Chinese Malaysian community. Being the second-largest ethnic group in Malaysia, the Chinese’s negative response to the initiative has generated some implications for the country’s socio-political order. Sin Chew Daily, the first newspaper to break the news, was accused by then Finance Minister Lim Guan Eng of stirring fears among the Chinese community. Lim’s condemnation of the Chinese daily and the manner in which the whole Jawi-Khat episode played out have raised questions over the roles of Chinese newspapers vis-à-vis their counterparts of other languages in the reportage of the JawiKhat move. Thus, a study on the ways three top vernacular-language newspapers in Malaysia, namely, Sin Chew Daily, The Star and Harian Metro, covered this issue, was conducted. The extent of news coverage, news sources, news frames and valence of the reports were analysed. The research findings reveal that each of the newspapers framed the Jawi-Khat controversy differently. Sin Chew remains a classic ethnic newspaper, having reported extensively on the issue and actively pursued the voice of opposition of various stakeholder groups towards a policy that impacts on Chinese education, a key area vital to the Chinese community. Otherwise, the three newspapers have, to varying degrees, performed the interpretive function within a controlled media landscape and attempted to deescalate conflicts and misunderstanding arising from the Jawi-Khat move.